IntellWheels: A Modular Development Platform for Intelligent Wheelchairs - Rodrigo Antonio Marques Braga (2011)
Intelligent wheelchairs can become an important solution to assist individuals suffering from disabilities and are thus unable to perform their daily activities using classic powered wheelchairs. This paper describes the concept and design of IntellWheels, a modular platform to facilitate the development of intelligent wheelchairs through a multi-agent system paradigm. In fact, modularity is achieved not just in the software perspective, but also through a generic hardware framework, which was designed to fit, in a straightforward manner, almost any commercial powered wheelchair. Experimental results demonstrate the successful integration of all modules in the platform, providing a safe motion to the intelligent wheelchair. Furthermore, the results achieved with a prototype running in autonomous mode, in a simulated and mixed reality environments, also demonstrate the potential of our approach. Although some future research is still necessary in order to fully accomplish its objectives, preliminary tests have shown that IntellWheels will be able to effectively reduce user's limitations, offering them a much more independent life.